Implementation Of Construction Safety Management System on The Building Project of Haji Hospital Of Surabaya - Hoiri, Muhammad; Setiawan, M Ikhsan; Wulandari, Diah Ayu Restuti (Malikussaleh University, Aceh, Indonesia, 2022)
Safety and accidents at work are the most serious thing to note, on building projects stroke center at Haji Hospital of Surabaya is still a lot of workers are less aware and less understanding about the safety and accidents caused due to neglect of the problem of workplace accidents. It is necessary to analyze the implementation of safety management system construction as well as the influence of the cost of the implementation of the project. This research method uses quantitative description based on the analysis about the application of the safety management system of construction on building projects stroke center Haji Hospital Surabaya, data collection through questionnaires (primary) which is distributed to 30 respondents consisting of the executive team (contractor), supervisory (MK) project and also some of the foreman of the workers, and observation and also documentation, where data is the results of the questionnaire were analyzed using the software IBM SPSS version 25, looking for the results of the multiple linear regression, T-test, an F-test. The results of linear regression analysis, T-test and F test obtained the value of T count T table where X1 = 3,071, X2 = 5,5658, X6 = 3,006 and X7 = 3,560 and F count= 54,308 F table = 2,46, the meaning that the variable of X1, X2, X6 and X7 are significant to application of safety management of the construction with the cost of implementation of construction projects